Post-traumatic stress disorders among children and adolescents in conflict-affected zones of Amhara region, February 2022 - Gebeyaw Biset; Gebeyaw Biset; Debrnesh Goshiye; Negesse Melesse; Mekonnen Tsehay (Frontiers in Psychology, 2023)
BackgroundTo date, conflict is causing extreme social crises worldwide, with children representing the most vulnerable group, often experiencing severe trauma and violence in conflict-ridden areas. Posttraumatic stress disorders (PTSDs) are the most widely reported psychological problem in the aftermath of conflict. However, less attention has been given to children living in conflict-prone areas of the world.ObjectiveThe present study aimed to assess posttraumatic stress disorders among children and adolescents in conflict-affected zones of the Amhara region in Ethiopia from January to February 2022.MethodA community-based cross-sectional study was employed from January to February 2022. A multistage random sampling technique was employed to recruit the study participants. A structured interviewer-administered questionnaire was designed to collect the desired data. Data were verified, coded, and entered into EpiData version 3.1 and analyzed using SPSS version 24 statistical software.ResultA total of 846 children with a response rate of 94.33% were screened for trauma. Subsequently, 557 (69.80%) children had experienced trauma. Of these 557 children who had experienced trauma, 203 (36.45%) developed posttraumatic stress disorders. Based on these results, this study recommends that mass screening of children and adolescents for posttraumatic stress disorders and rehabilitation services be undertaken, including resilience training and psychosocial support.